Total Thyroidectomy as Therapeutic Approach to Hyperthiroidism. Indications, Outcome and Complications - Sánchez Beorlegui, Jesús (1999)
OBJECTIVE: To compare the morbidity of total thyroidectomy (TT) and subtotal thyoidectomy (ST) in the management of hyperthyroidism. MATERIAL AND METHODS: A retrospective study of 350 cases of thyroidectomies performed at the Service B of Surgery at the Hospital Clínico Universitario Lozano Blesa, Zaragoza, Spain, from 1975 to 1996. Clinical diagnosis was always "hyperthyroidism". The main outcome measures were parathyroid morbidity (recurrent laryngeal nerve palsy, infections and hemorrhages), length of hospital stay, relapses and re-operations. RESULTS: Among 350 thyroidectomies done, 71 were TST and 279 were TT. Both techniques exhibited similar results, except for a higher incidence of recurrent laryngeal nerve palsy in the early postoperative period. CONCLUSIONS: TT was a good approach for hyperthyroidism because it prevented recurrences and had a low morbidity, with a minimal risk of complications.